2020
DOI: 10.1186/s40545-020-00262-y
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the factors influencing healthcare providers’ burnout during the outbreak of COVID-19 in Jordanian hospitals

Abstract: Background Coronavirus disease (COVID-19) is an infectious disease caused by a newly discovered coronavirus. The nature of healthcare providers’ occupation puts them at an increased risk of getting any contagious disease, including COVID-19. They are on the front line of the COVID-19 outbreak response and as such are at risk of contracting this virus. The infectious disease started from China in December 2019 and spread rapidly throughout countries, including Jordan. Especially, recent studies indicated that J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
71
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 26 publications
9
71
0
5
Order By: Relevance
“…Moreover, fear of infection, shortage of healthcare personnel, and adequacy of PPE were reported by physicians in our qualitative interviews to be major factors that a icted their physical and psychological wellbeing; thus, impacting their job satisfaction as well. This is also consistent with the ndings of a recent qualitative study that was conducted in Jordan among a sample of physicians, nurses, and pharmacists during the COVID-19 pandemic [49].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, fear of infection, shortage of healthcare personnel, and adequacy of PPE were reported by physicians in our qualitative interviews to be major factors that a icted their physical and psychological wellbeing; thus, impacting their job satisfaction as well. This is also consistent with the ndings of a recent qualitative study that was conducted in Jordan among a sample of physicians, nurses, and pharmacists during the COVID-19 pandemic [49].…”
Section: Discussionsupporting
confidence: 90%
“…They want to be recipients of updates and information relevant to their job. These preferences are not unique to our study population, and a lack of these elements in the work environment has been shown to contribute to healthcare worker burnout during the current pandemic (Algunmeeyn et al 2020). Critical care staff vary in their profession, therapy preferences and personal attributes, but they share a strong a professional identity, and strive to pursue activities that are consistent with this self-concept-especially during periods of increased professional demand (Ervin et al 2018;Yadav et al 2019).…”
Section: Discussionmentioning
confidence: 95%
“…The literature on emergency work has focused on the effects of working in critical situations, especially on burnout, as it poses a risk for healthcare workers [9,12]. As a concept, burnout refers to the emotional affect associated with feelings of frustration and powerlessness that develop in professionals' negative attitudes at work [13,14]. Individuals who work in healthcare services have been identified as a high-risk group for burnout, and the workers who have symptoms of this syndrome are less satisfied with their work activities than others [15,16].…”
Section: Introductionmentioning
confidence: 99%